Evaluasi Kebijakan Izin Reklame Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Tanjungpinang - Michelle Isabella; Ramadhani Setiawan; Chaerey Ranba Sholeh (Universitas Sains dan Teknologi Komputer, 2023)
The advertising permit policy is a problem that is still being faced by the City of Tanjungpinang. The background of this research is to see how the evaluation of the advertisement permit policy is carried out by the Investment and One-Stop Service Office of Tanjungpinang City based on Mayor Regulation Number 70 of 2021 concerning billboard organizers and procedures for advertisement permits. This study uses a descriptive method with a qualitative approach and uses the theory of William N Dunn (2003:429-499) with indicators: effectiveness, efficiency, adequacy, alignment, responsiveness, accuracy. The purpose of this research is to describe and analyze the licensing policy and advertising tax collection system, as well as the constraints on licensing and collection. In this case, by looking at licensing, arrangement and implementation of advertisements that have not run optimally in accordance with the mayor's regulation no. 70 of 2021 regarding the organizers and procedures for advertising permits. This research raises two issues: First, what is the advertising licensing policy in Tanjungpinang City. Second, what are the obstacles in licensing and structuring billboards in Tanjungpinang City. This study resulted in the conclusion that the permitting and arrangement of billboards carried out by DPMPTSP of Tanjungpinang City was not maximized, this was based on the results of research in the field, even though the BPPRD in particular had regulated and collected advertisement tax based on regional regulation number 2 of 2011 concerning regional taxes.